Дифузно-склерозуючий варіант папілярного раку щитоподібної залози у 14-річної дівчинки - Хоперія, В. Г.; Гузь, О. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
We report about a case of a rare diffuse sclerosing variant of papillary thyroid carcinoma in 14-year old girl. The clinicomorphological features of this disease were analyzed. Clinical, cytological and ultrasound findings, massive lymph node metastases suggest the main treatment should be radical surgery with maximally possible regional lymph nodes excision, radio-iodine therapy with following active monitoring due to high incidence of recurrence.